2016
DOI: 10.1016/j.annepidem.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in cumulative life-course socioeconomic position and social mobility in relation to new onset diabetes in adults—the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil)

Abstract: Accumulation of risk and social mobility were associated with NODM with gender-specific patterns, suggesting differences in mechanisms connecting life-course socioeconomic position and diabetes in men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(29 reference statements)
0
5
0
1
Order By: Relevance
“…There is a well‐established association between low socioeconomic status (SES) and poor cardiometabolic health (10,13‐29), and a number of studies have illuminated the relationship between cycles of low intergenerational educational attainment (IEA) and cardiometabolic outcomes, many of which demonstrate a worsening of obesity prevalence across generations (14,15,19,27‐32). However, the relationship between intergenerational socioeconomic mobility and the burden of obesity and MetS has not been clearly demonstrated for Hispanic/Latino communities (16,18,26), and there may be a stronger association for women, although few studies have examined this in a Hispanic/Latino population (14,16,17,20,27,29). Although SES is often measured by income, IEA is a more stable measure of SES across the life course, particularly for young adults and retirees, and is often a more effective marker in immigrant populations whose earning potential may be limited in their new country because of language barriers and lack of recognition for training or degrees earned in their home country (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…There is a well‐established association between low socioeconomic status (SES) and poor cardiometabolic health (10,13‐29), and a number of studies have illuminated the relationship between cycles of low intergenerational educational attainment (IEA) and cardiometabolic outcomes, many of which demonstrate a worsening of obesity prevalence across generations (14,15,19,27‐32). However, the relationship between intergenerational socioeconomic mobility and the burden of obesity and MetS has not been clearly demonstrated for Hispanic/Latino communities (16,18,26), and there may be a stronger association for women, although few studies have examined this in a Hispanic/Latino population (14,16,17,20,27,29). Although SES is often measured by income, IEA is a more stable measure of SES across the life course, particularly for young adults and retirees, and is often a more effective marker in immigrant populations whose earning potential may be limited in their new country because of language barriers and lack of recognition for training or degrees earned in their home country (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…There are important limitations in generalizing determinants of T2DM incidence from different populations [1][2][3][4][5][6][7]. This fact is partially explained by differences in obesity rates, lifestyle, health system resources, and access to medications for preventing the disease [3,8]. The association between marital status and various diseases has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…40,41 Two studies examined the association between diabetes and participants' socioeconomic trajectory between childhood and adulthood. In the ELSA-Brasil study, diabetes risk was highest in the persistent low and declining socioeconomic groups, 42 suggesting that socioeconomic position in adulthood, but not childhood, was inversely associated with diabetes. In the WHO-SAGE study, among men only, prevalence of self-reported diabetes was highest in the declining and persistent high socioeconomic groups, suggesting that childhood socioeconomic position is positively associated with risk of diabetes, independent of adult socioeconomic position.…”
Section: Diabetes and Impaired Fasting Glucosementioning
confidence: 99%